Criss-cross pulmonary arteries in common arterial trunk – Implications to management and outcome - Magdi H. Yacoub; Mohamed Nagy; Hatem Hosny; Ahmed Afifi; Amr El Sawy; Ahmed Mahgoub; Hedaia Abdullah; Soha Romeih; Mahmoud Shehata; Abdelrahman Elafifi (International Journal of Cardiology Congenital Heart Disease, 2023)
Objectives: To investigate the incidence, types and pathophysiology of criss-cross pattern of the proximal pulmonary arteries in common arterial trunk and its influence on management and outcomes. Methods: Retrospective review of all patients with common arterial trunk who underwent Aswan Truncus Operation with regard to the origin and course of the proximal pulmonary artery branches as defined by 3D segmented models pre, immediately and 1 and 2 years after operation. Results: Between January 2019 and September 2022, 39 patients (19 males, aged 1–12 months) underwent the Aswan Truncus Operation. 18 patients (46%) had criss-cross arrangement of the proximal pulmonary artery. The mortality, ICU and hospital stay were not affected by the presence or absence of the criss-cross pattern. However, following operation in the criss-cross group, there was evidence of different degrees of kinking and twisting of the right pulmonary artery. This resulted in severe narrowing which required stenting or reoperation at different stages (1 during ICU stay and another after 1 year). Separate origin of the left pulmonary artery (Criss-cross Type 2) from a long stenotic ductus arteriosus required resection of the stenotic segment followed by anastomosis to the right pulmonary artery recreating a 60° angle of bifurcation. Conclusion: Criss-cross pattern of proximal pulmonary arteries is common in patients with common arterial trunk. Pre-operative diagnosis and tailored approaches of repair are required to prevent late complications.